Long-Term Effects of Experimental Human Endotoxemia on Immune Cell Function: Similarities and Differences With Sepsis. Issue 6 (June 2019) - Rodriguez-Rosales, Yessica Alina; Kox, Matthijs; van Rijssen, Esther; van Cranenbroek, Bram; van Welie, Marina; Pickkers, Peter; Joosten, Irma; Koenen, Hans J.P.M.
Abstract : ABSTRACT: Sepsis is the cause of more than 5.3 million deaths per year, and novel immunotherapeutic strategies are highly warranted. Human models that mirror sepsis immunology are instrumental to this aim. The response to endotoxin in humans during the first 24 h captures many hallmarks of the inflammatory response observed in sepsis. However, the long-term immunologic effects of human experimental endotoxemia have been sparsely studied and could be determinant for the use of this model in sepsis therapy research. In the present work, we studied the immune-composition of healthy subjects challenged with endotoxin (1 ng/kg) 4 h, 2 days, and 20 days post administration by flow cytometry to study the effects on innate and adaptive immune system, and compared it with the immune-composition in patients during the first 9 days after onset of septic shock. We found several differences and similarities between these groups. Experimental endotoxemia resulted in an increase in absolute numbers of intermediate monocytes, which also displayed lower human leucocyte antigen expression 20 days post endotoxin. These changes differed with those observed in septic shock patients. Another long-term effect of experimental endotoxemia was elevated numbers of effector CD8 + cells and an increased percentage of proliferating and cytokine expressing CD8 + cells, and these phenomena were also present in sepsis patients. In conclusion, despite considerable differences, experimental endotoxemia captures several long-term aspects of sepsis immunology, specifically the behavior of CD8 + T cells, which may eventually aid the development of new therapies for sepsis patients. Abstract : Supplemental Digital Content is available in the text